Syphillis in Prague - Kuklová, I. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2003)
Since 1990 we have observed a gradual steady increase of syphilis incidence inthe Czech Republic, especially in larger cities and in border regions. In 2001, the total number of notified syphilis cases reached 1 376. Syphils rate has risen from 1.6 per 100 000 inhabitants in 1990 to 13.7 per 100 000 inhabitants in 2001, which represents an 8-fold increase. The aim of the studywas to review the hospitalization records of patients diagnosed with syphilis in Prague between 1999 and 2001. A total of 243 syphilis patients (92men and 151 women) were diagnosed and treated at our department. Out of theabove mentioned 151 women, 63 were pregnant. 18.9% patients, 15.2% women and 25% men presented as a result of partner notification. Symptomatic syphilis was seen in 45 (48.9%) men and 22 (14.6%) women. Dark field microscopy was positive in twenty (8.2%) cases. A total of thirty patients suffered from genital discharge. Three patients had gonorrhea, two chlamydial infection. All the patients were HIV negative at the time of syphilis diagnosis. By the means of questionnaire inquiry, we obtained information about demographic and behavioural characteristics of our patients.
Keywords: Bolezen, prijava; Czech Republic; Češka republika; Dejavniki tveganja; Disease Notification; Epidemiology; Praga; Prague; Prevalenca; Prevalence; Risk Factors; Sifilis; spolne bolezni; Syphilis